2023
DOI: 10.1088/1361-6463/ace2d0
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent axial fluid model of the Hall thruster discharge and its plume

Abstract: The standard time-dependent three-fluid model found in the literature is here enhanced by extending the physical
domain beyond the cathodic surface into the far plume, and improving the modelling of some physical phenomena.
The neutral momentum equation, azimuthal electron inertia, the neutral energy equation, and the ion energy equation
are progressively included to conform a suite of five models.
Fully stationary solutions are benchmarked against those of a purely stationary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…First, without the electron inertia term, solutions from the finite-difference approach have been verified to yield the same solution as the former Runge-Kutta shooting method in [1][2][3]. And second, with EAI included and fixed operation conditions, solutions of the present stationary model have been successfully compared with stationary solutions from a time-dependent model [49].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…First, without the electron inertia term, solutions from the finite-difference approach have been verified to yield the same solution as the former Runge-Kutta shooting method in [1][2][3]. And second, with EAI included and fixed operation conditions, solutions of the present stationary model have been successfully compared with stationary solutions from a time-dependent model [49].…”
Section: Discussionmentioning
confidence: 86%
“…This second verification case is specially interesting, since time-dependent models work with the absolutely different framework of partial differential equations (PDEs) and, thus, numerical methods used in this work can be hardly compared with those in, e.g. [36,49]. An evidence of the different mathematical nature of steady and time-dependent problems is that working with PDEs avoids the problem of dealing with internal singularities, which is one of the main challenges of the stationary model.…”
Section: Discussionmentioning
confidence: 99%
“…From the above we can see that the current density can be supposed based on the electron number density ne, the magnetic field B and the electric field E. Measurements with probe and PIC simulations are both auxiliary techniques to detect these three parameters and typical distributions of them in conventional Hall thrusters can be drawn from [9,[12][13][14]21], from which we can infer certain characteristics of the Hall drift current: it likely exhibits a singular peak distribution within the channel of the Hall thruster, possibly following a three-dimensional Gaussian distribution along the channel. This peak is anticipated to be proximate to the exterior of the channel exit and the outer wall surface of the channel.…”
Section: Distribution Of the Hall Drift Current 231 Typical Distribut...mentioning
confidence: 99%
“…Interestingly, near the anode, u θe ≈ c e . Different works on 1D fluid models by Ahedo and co-workers [35,45,46] have demonstrated that (1) the electron azimuthal inertia matters near the anode for…”
Section: The Electron Momentum Equationmentioning
confidence: 99%
“…The contribution of M zθe (both as inertia and as gyroviscosity) near the anode has been observed previously in simulations with 1Dz fluid [35], 1Dz PIC [24] and 2Dzθ PIC [34] models. Parametric studies [35,46] show that these contributions near the anode are favored by large values of the locally Hall parameter and become nonmarginal only when the local electron density decreases much, thus locally increasing the electron drift velocities. Therefore, on the one hand, these effects require a good assessment of both electron-neutral collisionality and anomalous diffusion neat the anode.…”
Section: The Electron Momentum Equationmentioning
confidence: 99%